Hybrid Wetting Surface with Plasmonic Alloy Nanocomposites for Sensitive SERS Detection - Wang, Shanjiang; Su, Dan; Zhou, Huanli; Jiang, Xiaohan; Zhang, Xiaoyang; Zhang, Tong (Molecules (Basel, Switzerland), 2023)
In this paper, a hybrid wetting surface (HWS) with Au/Ag alloy nanocomposites was proposed for rapid, cost-effective, stable and sensitive SERS application. This surface was fabricated in a large area by facile electrospinning, plasma etching and photomask-assisted sputtering processes. The high-density ‘hot spots’ and rough surface from plasmonic alloy nanocomposites promoted the significant enhancement of the electromagnetic field. Meanwhile, the condensation effects induced by HWS further improved the density of target analytes at the SERS active area. Thus, the SERS signals increased ~4 orders of magnitude compared to the normal SERS substrate. In addition, the reproducibility, uniformity, as well as thermal performance of HWS were also examined by comparative experiments, indicating their high reliability, portability and practicability for on-site tests. The efficient results suggested that this smart surface had great potential to evolve as a platform for advanced sensor-based applications.